Evaporation controlled particle patterns in a polymer droplet. Issue 30 (30th March 2017) - Zhang, Chongfeng; Akcora, Pinar
Abstract : The unusual formation of particle stripes is observed in evaporating polymer drops containing mixtures of microspheres and nanoparticles. Concentric rings are obtained when capillary shear and Marangoni flows are balanced at low evaporation rates. Abstract : Colloidal microspheres in aqueous polymer drops were previously shown to spatially order into stripes upon drying due to a combination of the phase separation of highly bridged particles and the Marangoni flow effect. In this work, the dynamics of contact line movement of a colloidal–polymer droplet under varying evaporation conditions was monitored in real-time. It was shown that slowing the evaporation rate decreased the contact angle and the resulting stationary contact line enabled a balance between capillary shear and Marangoni flows. Thus, particle deposition into concentric rings was dependent on contact line velocity and receding contact angle. Adding nanoparticles into a polymer–microparticle mixture did not perturb the hydrodynamic flows, subsequently nanoparticles were observed to deposit onto multiple rings and striped patterns. The presented colloidal assembly which is controlled by the bridging of chains between polymer-adsorbing particles was also shown to be effective in the formation of lines parallel to the contact line prepared in a dip-coating process.